Binge Watching, Para Social Relationships and Psycho Social well-Being in Early Adults - Shaker, Kashmala Shaheen; Bukhari, Syeda Razia (Journal of Development and Social Sciences, 2025)
This study aimed to examine the relationship between binge-watching, parasocial relationships, and psychosocial well-being in early adults, with a focus on the mediating role of parasocial relationships.The rise in binge-watching behavior among young adults has been associated with the formation of parasocial relationships, potentially impacting mental and social well-being. This study explores these interrelations in the context of early adulthood. Using a correlational research design, a purposive sample of 250 university students (88 males, 162 females; M = 1.65, SD = 0.48) aged 18–30 years was recruited from universities in Rawalpindi and Islamabad. Standardized scales were used to assess binge-watching engagement, parasocial interaction, and psychosocial well-being. Data were analyzed using Pearson correlation and mediation analysis. Binge-watching was positively correlated with parasocial relationships and negatively with psychosocial well-being. Parasocial relationships significantly mediated this relationship. Demographic variables showed no significant association. Interventions promoting balanced media use and emotional regulation are recommended to enhance psychosocial well-being in early adults. Data was collected from three universities only which was a limitation as the data cannot be generalised on students of other universities. Data was not collected from males and females equally. In further studies gender difference could be one dimension to be researched on. For future research, evaluation criteria can be altered in accordance with the sample, or the sample population might be given a brief introduction to the study.